A food multi-mix to address malnutrition amongst primary school children living in Eatonside - Oosthuizen, Delia (My University, 2006)
The primary objective of this study was to formulate a multi-mix, which could supply at least one-third of the daily requirements of primary school children, aged six to 13 years. The secondary objective was to ensure the adherence to the criteria of multi-mix formulation, which included affordability, convenient, palatability, culturally acceptable and cost effective, whilst providing high nutritional value for the specified target group. The nutritional criteria included the Index Nutrient Quality (INQ) and Energy Density (ED) requirements, for a specific target group. This study was conducted in Eatonside, an informal settlement situated in Gauteng. A situational analysis previously conducted in Eatonside (Napier 2003) showed that the children between the ages of six and 13 years, were 17% underweight (weight-for-age -2SD from the reference NCHS median), 12,7% were wasted (BMI-for-age -2SD) and 18% stunted (height-for-age -2SD). With the nutritional requirements of children and the most consumed food list, the multi-mix formulation began. Foods from the Top 20 list (Napier 2003), were combined with the ingredients most common within the households, and vegetable gardens already established . Estimated nutritional values were calculated using the food composition tables of South Africa. The ingredients were prepared and chemically analysed to determine the experimental nutritional value and to assess if the nutritional objectives were being achieved. The multi-mix was then combined with other commonly consumed ingredients to form recipes and sensory evaluated by professionals and the primary school children to assess the acceptability of the multi-mix and recipes. The multi-mix and recipe products were then sent for shelf life testing to assess its storage time at room temperature. The results from the nutritional analyses showed nutrient values to be above 30 percent of the Estimated Average Requirements (EAR). The INQ of the targeted nutrients was above 1,0 and the ED at 3,7kcal/g, which was within the 3,6-4,5 kcal/g requirements. The sensory evaluation for the multi-mix recipes had proved favourable response to snack items with preference for sweet products. The final evaluation session resulted in scores of 83.9 percent preference to the biscuit with the sweet muffin scoring 94.5 percent liking, whilst the savoury muffin at 73.1 percent. The average scores for all three recipes were above 80 percent. The multi-mix had a shelf life of minimum one-month, the biscuit, seven days and muffins, only 24 hours, at room temperature. The objectives of cultural acceptability had been achieved through the positive response from the use of ingredients within the community. The multi-mix had been cost effective as the final cost of R1.55, was within the R2.90 spent per person per day, for all three meals (Oidewage-Theron eta/. 2005). Further studies need to be conducted in order to implement the multi-mix into an intervention within the community to assess the effect on nutritional status. This study, aimed to reduce the underlying cause of malnutrition, food insecurity, by improving the nutritional status of children aged six to 13 years with the strengthening of food intake, through the combination of various scant ingredients, a multi-mix, providing maximum nutritional value with small quantities. An advantage of the multi-mix is a lower cost when compared with tablet supplementation on the market and versatility in relation to various recipes.
M. Tech. (Hospitality and Tourism, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Malnutrition; Nutrient content; Nutritional supplements; Children; Recipes; 614.59390968; Malnutrition in children -- South Africa; Nutrition evaluation; Dietary supplements; Nutrition -- Requirements